O programa Saúde da família na prevenção de situações de complexidade : o exemplo da AIDS - Silva, Ana Cláudia do Espírito Santo (2004)
Methodology: In the first part of this work a research was carried through became fullfilled a descriptive study on the population of the medical professionals, nurses and health agents who compose the teams of the PSF of the city of Fortaleza. The instrument of collection of data were an adaptation of the questionnaire used in the national research concerning the Sexual Behavior of the Brazilian Population, carried through for the Health department, in the year of 2000. At as a moment a qualitative study with the accomplishment of focal groups was made, with this same population, that approached subjects related to the AIDS and sexuality. After bibliographical survey of the authors who present works of relevance related to the subject we arrive at the following axles that had guided our look had been: I) practical sexual as practical the social ones; Practical II) the social construction of the sexual ones follow the dynamism of the cultures and practical III) the sexual ones are lived by multidimensionais.Resultados citizens of the first stage: the research pointed that practical sexual between people of the same sex and existence of extramarital relations widely it was rejected by the participants of the research. Although almost all to have carried through training in AIDS, some had disclosed that the illness if can catch using public bathrooms, becoming use of the masculine or feminine condom in the sexual relation or using the same place setting of contaminated people. The majority pointed that the condoms are ackward but exactly thus it must be used to prevent aid. Results of the second stage: The study in it disclosed a conception to them mythical that involves aspects related to the illness placing it, almost always, as a thing of the other; the condom in turn, acquired a status of instrument of intermediation in the relation of being able; glimpsing also a naturalization in the interpersonal relations mediated by these relations of being able. Conclusions: It was observed that it has a economic difference partner enters the professionals of the team of the PSF thus characterizing a difference of classrooms and sort permeado for intrinsic relations of being able. We saw that the opinions of these professionals, although all the armory of specific knowledge and petitioned training, are crossed by one strong biomedical influence of asepsis of the bodies, characterized for a set of experiences and values that are not differentiated very of the population in general.